Evaluation of Heavy Metals Concentration in Different Local Brands of Selected Cleanser Products - Ab Manan, Wan Noni Afida; Mohamad, Liyana Nafeesa; Yusoff, Siti Fairuz (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Heavy metals' concentration in cleanser products can cause health hazards. The present study was conducted to evaluate the concentrations of heavy metals in different local brands of selected cleanser products with special emphasis on their health risk assessment. Five heavy metals including Pb, Cu, Cd, Zn and Hg were quantified in different brands using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). All cleanser samples were labelled as Sample A, B, C, and D. Risk to consumers' health was determined using systemic exposure dosage (SED) and margin of safety (MoS). On comparative basis, Sample A had the highest concentration of Zn, Pb and Hg (12.350 ± 0.04, 0.020 ± 0.001, 0.710 x 10-3 ± 0.16 x 10-3 mg/kg, respectively), whereas Sample D had the highest level of Cu at 0.190 ± 0.02 mg/kg. SED and MoS values were estimated for 50 % and 100 % bioaccessibility for all the samples. Based on the results, MoS values for samples B, C and D were greater than 100 mg/kg/d , which showed that the evaluated samples were safe for use. Nevertheless, in Sample A, the MoS values for Pb and Zn at 100 % bio-accessibility were below 100 mg/kg/d, which denoted that the product is not safe for use, particularly concerning the heavy metals contamination. Hence, regular use of these cleanser products would result in accumulation of the heavy metals in the human body which can cause risks for human health